Arterial stiffness in acute COVID‐19 and potential associations with clinical outcome. (21st March 2021) - Schnaubelt, S.; Oppenauer, J.; Tihanyi, D.; Mueller, M.; Maldonado‐Gonzalez, E.; Zejnilovic, S.; Haslacher, H.; Perkmann, T.; Strassl, R.; Anders, S.; Stefenelli, T.; Zehetmayer, S.; et al.
Abstract: Background: Coronavirus disease 2019 (COVID‐19) interferes with the vascular endothelium. It is not known whether COVID‐19 additionally affects arterial stiffness. Methods: This case–control study compared brachial‐ankle pulse wave (baPWV) and carotid‐femoral pulse wave velocities (cfPWV) of acutely ill patients with and without COVID‐19. Results: Twenty‐two COVID‐19 patients (50% females, 77 [67–84] years) were compared with 22 age‐ and sex‐matched controls. In COVID‐19 patients, baPWV (19.9 [18.4–21.0] vs. 16.0 [14.2–20.4], P = 0.02) and cfPWV (14.3 [13.4–16.0] vs. 11.0 [9.5–14.6], P = 0.01) were higher than in the controls. In multiple regression analysis, COVID‐19 was independently associated with higher cfPWV ( β = 3.164, P = 0.004) and baPWV ( β = 3.532, P = 0.003). PWV values were higher in nonsurvivors. In survivors, PWV correlated with length of hospital stay. Conclusion: COVID‐19 appears to be related to an enhanced PWV reflecting an increase in arterial stiffness. Higher PWV might be related to an increased length of hospital stay and mortality. Abstract :